Effect of the differential discount value on the purchase prediction: an approach from associative learning - Rodríguez González, Liliana Yamile; Aristizábal Cuéllar, José Alejandro; Tejada Herrera, Héctor Julián (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
The purpose of this study was to explore the effect of changing the context in which a product with different discount values has been associated with purchase prediction. Participants were trained in a learning task where they had to predict the probability of a result (purchase of a product) based on different images (products), presented in different contexts (stores). In store A, product X associated with different discount values (50%, 30%, 0%) and the product Z associated with a constant discount (30%) were presented. In store B, product Y was presented without discount (0%). Control products without discount were presented in each context (F1 and F2). The results indicate that the differential discount value is context dependent, which means that the probability of purchase is greater when the product with a variable discount is presented in the same store where the association with multiple discounts was previously learned. This effect was less with the product with constant discount and was not observed in the product without discount. The implications of these findings are discussed considering the effectiveness of discount promotional strategies in stores.